2011
DOI: 10.1016/j.biomaterials.2011.05.073
|View full text |Cite
|
Sign up to set email alerts
|

A phosphate-dependent shift in redox state of cerium oxide nanoparticles and its effects on catalytic properties

Abstract: Cerium oxide nanoparticles (CeNPs) have shown promise as catalytic antioxidants in cell culture and animal models as both superoxide dismutase and catalase mimetics. The reactivity of the cerium (Ce) atoms at the surface of its oxide particle is critical to such therapeutic properties, yet little is known about the potential for a protein or small molecule corona to form on these materials in vivo. Moreover Ce atoms in these active sites have the potential to interact with small molecule anions, peptides, or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
264
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(283 citation statements)
references
References 35 publications
16
264
1
2
Order By: Relevance
“…Previous work has shown that the superoxide dismutase activity of nanoceria is inhibited by simple inorganic phosphate ions. 34 However, its oxidase activity is not significantly affected as shown in the current study. Only when DNA with poly-phosphate backbone is used, its oxidase activity was inhibited.…”
supporting
confidence: 51%
“…Previous work has shown that the superoxide dismutase activity of nanoceria is inhibited by simple inorganic phosphate ions. 34 However, its oxidase activity is not significantly affected as shown in the current study. Only when DNA with poly-phosphate backbone is used, its oxidase activity was inhibited.…”
supporting
confidence: 51%
“…However, its antioxidative quality is only effective when the two enzyme-like activities of CeONP are coordinated, that is, the H 2 O 2 decomposition rate should be equal to or greater than its generation rate. According to recent reports, many factors such as particle size, Ce 3 þ /Ce 4 þ ratio, 32,43,50 buffer species 51 and pH conditions 51,52 could affect the enzyme-mimetic properties of CeONP.…”
Section: The Multi-enzyme Mimetic Activities Of Ceonpmentioning
confidence: 99%
“…For buffer species, exposure of CeONP to phosphate buffer would result in a decrease in SOD-mimetic activity and an increase in catalase-mimetic activity. 51 Given that phosphate is a basic substance in biological systems, its impact on the activity of CeONP should be taken into account when CeONP is used in cell culture or animal studies. However, the ability to reverse the 'poisoning' of the SOD-mimetic activity in vivo can be investigated in future studies.…”
Section: The Multi-enzyme Mimetic Activities Of Ceonpmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, CuZn-SOD or some appropriate electron donors can greatly improve the SOD mimetic activity of nanoceria. [21] A study conducted by Singh et al [89] reported that nanoceria lost SOD activity when it was exposed to high concentration of phosphate anions due to the binding of phosphate anions to cerium. As a result, cerium phosphate blocked the redox cycling between Ce 3+ and Ce 4+ , which was essential for antioxidant/ catalytic activity of nanoceria.…”
Section: Parameters Influencing the Enzyme Mimetic Activities Of Nanomentioning
confidence: 99%